Empowering Financially Vulnerable Consumers through Digital Marketing: Enhancing Access to Inclusive Banking Services - Ngobeni, Beryl (University of the Witwatersrand, Johannesburg, 2024)
Financially vulnerable consumers in South Africa face barriers to accessing inclusive banking services, limiting their financial participation. This study explores how digital marketing can bridge this gap by enhancing engagement and promoting financial literacy. Using a qualitative research approach, nine semi-structured interviews and two focus group discussions were conducted with consumers and banking professionals in Johannesburg and Limpopo, South Africa. The Financial Capability Framework was applied to assess financial knowledge, skills, attitudes, and behaviours. Findings show that personalized, culturally relevant digital marketing campaigns improve engagement, while multi-channel strategies, such as social media, mobile banking, and Unstructured Supplementary Service Data (USSD), enhance accessibility. However, challenges like fraud, low digital literacy, and high data costs persist. Financial education through digital campaigns and community outreach builds trust, while zero-rated services and AI-driven personalization improve access for low-income consumers. The study proposes a Digital Financial Inclusion Framework (DFIF) to guide banks in developing inclusive, trust-driven strategies. By addressing barriers and leveraging digital tools, banks can foster a more equitable financial ecosystem. This research offers actionable insights for policymakers, financial institutions, and digital marketers to advance financial inclusion in South Africa. It also presents tiered implementation strategies for banks and explores future applications of emerging technologies.
A research report submitted in fulfillment of the requirements for the Master of Management in the field of Digital Business, in the Faculty of Commerce Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Financial inclusion; digital marketing; financially vulnerable consumers; South Africa; SDG-8: Decent work and economic growth; SDG-9: Industry, innovation and infrastructure